‘I was like, this is gonna hurt’: Implementing self-sampling of dried blood spots to measure HIV viral load - Jennifer V. Chavez; Leah Davis Ewart; Ozair Ilyas; Delaram Ghanooni; José E. Diaz; Lindsay Atkins; Richard Ramos; Adriana Hernandez; Alex Stewart; Keith J. Horovath; Sabina Hirshfield; Adam W. Carrico (PLoS ONE, 2025)
Background Sexual minority men (SMM) with HIV who use stimulants may experience greater difficulties with antiretroviral therapy adherence which amplifies risk for unsuppressed HIV viral load (VL). Remote monitoring of VL could support efforts to rapidly respond to sub-optimal adherence. Methods This qualitative study enrolled 24 SMM with HIV who use stimulants to examine experiences with two different dried blood spots (DBS) self-sampling devices (i.e., Tasso-M20 vs. HemaSpot HD) to measure VL. Participants were asked to complete self-sampling of DBS using both devices, and then participated in a 45-minute semi-structured interview. Interviews focused on ease of use, device preference, experiences with receiving and mailing kits, and barriers to participating in research. A thematic analysis was conducted to analyze interview transcripts. Results Twenty-two participants (92%) returned the Tasso-M20 and 21 (88%) returned the Hemaspot HD devices. Among the 22 participants that completed qualitative interviews, twenty-three codes were identified and collapsed within seven themes. Preferences for devices were based on convenience, pain and prior experiences with finger-pricking technology. Participants emphasized that clearer instructions with contingency plans for self-sampling of DBS would improve the user experience with self-sampling of DBS. Intersectional stigma (e.g., HIV, sexual minority status, and substance use) was noted as an important consideration in implementing self-sampling of DBS. Promoting decision making, or the option to choose sampling method based on personal preferences, may improve engagement and likelihood of DBS completion. Conclusions Findings will guide the broader implementation of self-sampling of DBS to optimize VL monitoring in SMM with HIV who use stimulants. Routine HIV viral load (VL) testing is recommended to assess the success of anti-retroviral therapy (ART) and identify individuals who may be experiencing difficulties with adherence to optimize rates of viral suppression [1]. The U.S. Department of Health and Human Services (HHS) Panel on Antiretroviral Guidelines for Adults and Adolescents recommends routine VL monitoring every three to six months after initiating ART. For those with optimal ART adherence and consistently suppressed VL for more than one year, VL monitoring is recommended every six months [2]. A convenience sample of SMM with HIV who use stimulants were recruited via email using an existing consent-to-contact database of individuals interested in potential research participation. Recruitment included up to three emails, sent between March and June 2022, which detailed the study purpose and provided a link to the online study screener. Interested individuals who clicked on the provided link were directed to a brief screener consent page before reaching the screener survey. Eligible individuals were a) cisgender man, b) aged 18 or older, c) comfortable reading and speaking English, d) US residency, e) reported ever having anal sex with a man, f) self-reported HIV diagnosis at least 90 days prior to screening, g) an active ART prescription AND < 90% past-month adherence on the 3-item Wilson measure in the past 30 days [21], h) screened positive for a moderate or severe stimulant use disorder (i.e., cocaine or methamphetamine) in the past 3 months with an abbreviated version of the National Institute on Drug Abuse (NIDA)-modified Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) [22], and i) ownership of an iPhone or Android smartphone. Individuals who met the eligibility criteria were contacted by study staff to schedule a Zoom assessment, where they received information about the study, completed informed consent, and provided contact information so that self-sampling DBS collection devices could be mailed to their homes.